America's Arab refugees vulnerability and health on the margins - Inhorn, Marcia C. (Stanford University Press, 2018)
America's Arab Refugees is a timely examination of the world's worst refugee crisis since World War II. America's Arab Refugees questions America's responsibility for, and commitment to, Arab refugees, mounting a powerful call to end the violence in the Middle East, assist war orphans and uprooted families, take better care of Arab refugees in this country, and provide them with equitable and affordable healthcare services.